The potential of Mulligan mobilization with movement and blood flow restriction training for lateral epicondylitis - I Dewa Gede Alit Kamayoga; A A I Ayesa Febrinia Adyasputri; I Putu Gde Surya Adhitya; I Made Dhita Prianthara; M. Widnyana; Anak Agung Gede Eka Septian Utama; I Putu Yudi Pramana Putra (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: One activity that might cause lateral epicondylitis is sports. The symptoms of lateral epicondylitis include pain, a loss of strength, and decreased functional status. To counteract this problem by applying mulligan mobilization with movement and blood flow restriction training. This study aimed to determine the potential of mulligan mobilization with movement and blood flow restriction training to alleviate the problems in lateral epicondylitis. Methods: This study uses a literature review by conducting data studies related to mulligan mobilization with movement, blood flow restriction, and lateral epicondylitis. The initial search in 4 databases found a total of 31 articles. After the selection, using inclusion and exclusion criteria obtained, 24 articles. Results: Based on some literature shows that mulligan mobilization with movement and blood flow restriction training effectively can engage descending pain inhibitory systems and increase muscle activation for strength and functional status effect. Conclusion: Providing mulligan mobilization with movement and blood flow restriction training could ease pain and improve hand grip strength and functional activity that occurs when lateral epicondylitis occurs.